1987
DOI: 10.1128/aac.31.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of beta-lactams on aminoglycoside uptake, bactericidal rates, and turbidimetrically measured growth inhibition in Pseudomonas aeruginosa

Abstract: In vitro studies of tircarcillin or cefsulodin combined with [3H]tobramycin were performed with Pseudomonas aeruginosa. The rate of bacterial killing, the uptake of tobramycin, and the effects on optical density were measured. Both ,I-lactams increased the uptake of subinhibitory concentrations of tobramypin. This result was quantitatively associated with a 2-to 4-h time-kill potentiation and confirmed earlier studies on the mechanism of J3-lactam-aminoglycoside synergy in Escherichia coil (P. H. Plotz and B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Bryan demonstrated that aminoglycoside-selected small-colony resistant mutants had respiratory transport enzyme changes that resulted in a marked reduction in the transmembrane potential (9). In a manner not yet understood, in the presence of an active beta-lactam there is a preservation of the high transmembrane potential in small-colony variants of P. aeruginosa (42).…”
Section: Once-daily Aminoglycosides In Animal Models Of Infectionmentioning
confidence: 99%
“…Bryan demonstrated that aminoglycoside-selected small-colony resistant mutants had respiratory transport enzyme changes that resulted in a marked reduction in the transmembrane potential (9). In a manner not yet understood, in the presence of an active beta-lactam there is a preservation of the high transmembrane potential in small-colony variants of P. aeruginosa (42).…”
Section: Once-daily Aminoglycosides In Animal Models Of Infectionmentioning
confidence: 99%
“…The combination of a ␤-lactam and an aminoglycoside allows for different mechanisms of bacterial killing (8,66,98,237). ␤-Lactam-mediated disturbance of the cell walls of Gram-negative bacilli facilitates passage of aminoglycosides into the periplasmic space (105,169).…”
Section: Synergymentioning
confidence: 99%
“…Most of these studies concluded that there was synergy but to an extent that proved to be highly strain dependent. While the exact mechanism of this synergy often remains uncertain, a number of pharmacological reasons have been proposed, such as the enhancement of the uptake of the companion antibiotics by colistin through its destabilizing effects on the outer membrane (15) or the increased diffusion of entry of aminoglycosides through the peptidoglycan when altered by ␤-lactams (16).…”
mentioning
confidence: 99%